2015
DOI: 10.1021/acscatal.5b00173
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Activity and Stability of TiO2-Coated Cobalt/Carbon Catalysts for Electrochemical Water Oxidation

Abstract: TiO2-coated Co/C catalysts prepared by atomic layer deposition (ALD) were used to study the effect of TiO2 overcoating on a Co/C catalyst for electrochemical water oxidation. The Co/C catalyst with a thin-layer overcoating of TiO2 (ALD­(TiO2)-Co/C) demonstrated 2.5 times higher turnover frequency (TOF) than the Co/C catalyst for the reaction. The TOF of the ALD­(TiO2)-Co/C catalyst increased when the ALD­(TiO2) coating cycle number was increased from 5 to 60. In addition, the stability of the 60 cycle ALD­(TiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 62 publications
(98 reference statements)
0
36
0
Order By: Relevance
“…Therefore, it would be highly desirable to stabilize inexpensive supported non-sulfide base-metal catalysts for the aqueous-phase processes. We have recently reported that base-metal catalysts can be stabilized by overcoating with a layer of Al 2 O 3 or TiO 2 using atomic layer deposition (ALD) [28][29][30]. An Al 2 O 3 overcoat formed by ALD stabilized the copper particles against leaching and sintering for liquid-phase hydrogenation reactions [28].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it would be highly desirable to stabilize inexpensive supported non-sulfide base-metal catalysts for the aqueous-phase processes. We have recently reported that base-metal catalysts can be stabilized by overcoating with a layer of Al 2 O 3 or TiO 2 using atomic layer deposition (ALD) [28][29][30]. An Al 2 O 3 overcoat formed by ALD stabilized the copper particles against leaching and sintering for liquid-phase hydrogenation reactions [28].…”
Section: Introductionmentioning
confidence: 99%
“…The porous structures of carbon and zeolite supports enable a high electrochemical surface area ( ECSA ) to be achieved for the electrocatalysts, which results in higher activity, though they have lower electrical conductivities than metal supports, which thereby reduces their overall efficiency . Further, the high electronegativity of carbon promotes acidity in the catalyst sites . To alleviate the problem of low electrical conductivity, the use of metal supports has been suggested .…”
Section: Introductionmentioning
confidence: 99%
“…Deposition of several layers of TiO 2 onto a surface of a Co/C composite significantly decreased the overpotential necessary to gain −10 mA cm −2 current density for HER, but also improved the stability of the composite in time. [ 58 ] Similar approach was used to protect an Al‐doped ZnO electrocatalyst. [ 59 ] The base of the composite was deposited using diethylzinc, trimethylaluminum, and water at 175 °C.…”
Section: Hydrogen Evolution Reactionmentioning
confidence: 99%